Towards establishing a scale for assessing the attractiveness of petroleum fiscal regimes – Evidence from Malaysia - Abdul Manaf, Nor Aziah; Mas'ud, Abdulsalam; Ishak, Zuaini; Saad, Natrah; Russell, Alex (Elsevier B.V., 2016)
This paper identifies a gap in the current literature relating to the attractiveness of petroleum fiscal regimes and suggests that establishing a measurement scale based on relevant factors drawn from the extant literature and on the perceptions of experts would complement the economic models currently in use and could become an industry standard.It will undoubtedly influence the petroleum fiscal policies and practices of petroleum producing countries.The methodology used involved a review of literature to identify factors that enhance the attractiveness of petroleum fiscal regimes; deploying experts to validate the appropriateness of the identified factors; conducting exploratory factor analysis and evaluating the internal consistency reliability of the construct's dimensions; performing confirmatory analysis for convergence and discriminant validity of the dimensions; and computing model fit indices to evaluate the goodness of fit of the four-factor correlated attractiveness petroleum fiscal regime scale. The results obtained suggest that a credible and manageable scale for assessing the attractiveness of petroleum fiscal regimes can be readily constructed.This research has taken the first important pioneering step in the construction of a globally applicable scale, the mechanics of which will require extension of our research, and consequently makes a significant contribution to policy making and literature.